2017
DOI: 10.1002/mgg3.315
|View full text |Cite
|
Sign up to set email alerts
|

Living with a rare disorder: a systematic review of the qualitative literature

Abstract: BackgroundIndividuals with rare diseases may face challenges that are different from those experienced in more common medical conditions. A wide range of different rare conditions has resulted in a myriad of studies investigating the specificities of the diagnosis in focus. The shared psychological experiences of individuals with a rare condition, however, have not been reviewed systematically.MethodsWe performed a systematic review, including qualitative studies on adults, published between 2000 and 2016. Pap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

26
234
0
14

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 231 publications
(274 citation statements)
references
References 59 publications
26
234
0
14
Order By: Relevance
“…Further, participants in this study took on the role of care coordinator in order to improve care continuity and fill gaps in healthcare provider communication deficits. Again, this is congruent with previous research with individuals with RDs (von derLippe et al 2017). Given that parents of children who are not-…”
supporting
confidence: 90%
See 1 more Smart Citation
“…Further, participants in this study took on the role of care coordinator in order to improve care continuity and fill gaps in healthcare provider communication deficits. Again, this is congruent with previous research with individuals with RDs (von derLippe et al 2017). Given that parents of children who are not-…”
supporting
confidence: 90%
“…Given the lack of knowledge, treatments, and research on RDs, many participants in this study had to actively seek out information on their child's disorder, which is not unusual for those in the RD community (Kesselheim et al 2015). In a systematic review of qualitative research about living with a RD, the notion of "expert patient" was identified (von der Lippe et al 2017). In our study, parents became "expert caregivers."…”
Section: Discussionmentioning
confidence: 99%
“…This is congruent with finite studies on parents' experiences with rare diseases (Galpin et al, 2017;Pelentsov, Laws, & Esterman, 2015). Compartmentalized care models within health and government supports are designed for periodic health incidents, not for complex disease trajectories such as complex rare NDDs (Grut & Kvam, 2013;von der Lippe, Diesen, and Feragen (2017). With unmet care needs, parents experienced pervasive demands and atypical family functioning.…”
Section: Discussionsupporting
confidence: 57%
“…Interestingly, while subjective health perception has been repeatedly identified as an important factor in relation to depressive symptoms in FD, the observed relation between organ complications and depressive symptoms has been less straightforward. We propose that impact of FD on patients' perceived health extends beyond the physical symptoms and complications, to more subjective factors such as uncertainty about the future, difficulties surrounding heritability and stigmatization [34,35]. In other words, complications and symptoms might have an effect on depressive symptoms, but the perception that patients have of their disease and the extent to which certain coping styles are employed will determine the individual outcome.…”
Section: Discussionmentioning
confidence: 99%